2020
DOI: 10.1186/s12889-020-08515-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of acute lower respiratory infection among children living in biomass fuel using households: a community-based cross-sectional study in Northwest Ethiopia

Abstract: Background: Childhood acute lower respiratory infection in the form of pneumonia is recognized as the single largest cause of childhood death globally accounting for 16% of the overall deaths. Some studies also reported a higher prevalence of childhood acute respiratory infection in Ethiopia, which ranges from 16% up to 33.5%. Concerning the risk factors, there are limited community-based studies in Ethiopia in general, and in the current study region in particular. Therefore, the present study was conducted t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 41 publications
4
47
1
1
Order By: Relevance
“…The predicted effect of the biomass-fuelled IBS intervention was not found to have a statistically signi cant effect on the risk of repeated childhood ALRI response among under 5 years old children in Northwest Ethiopia with an estimated AOR of 0.95 (95% CI: 0.89-1.02) compared with the continuation of an open burning TBS method. This nding mirrors the previous cross-sectional study, conducted as baseline part of this stove trial project, which reported that the odds of childhood ALRI did not show a signi cant association among children living in households with IBS when compared with children living in households with the TBS type with an estimated AOR of 0.78 (95% CI: 0.52-1.15)(23). Likewise, a recent policy research working paper reported no evidence that "Mirt" IBS intervention reduced the risk of respiratory symptoms among older children in rural Ethiopia(12).…”
supporting
confidence: 83%
See 3 more Smart Citations
“…The predicted effect of the biomass-fuelled IBS intervention was not found to have a statistically signi cant effect on the risk of repeated childhood ALRI response among under 5 years old children in Northwest Ethiopia with an estimated AOR of 0.95 (95% CI: 0.89-1.02) compared with the continuation of an open burning TBS method. This nding mirrors the previous cross-sectional study, conducted as baseline part of this stove trial project, which reported that the odds of childhood ALRI did not show a signi cant association among children living in households with IBS when compared with children living in households with the TBS type with an estimated AOR of 0.78 (95% CI: 0.52-1.15)(23). Likewise, a recent policy research working paper reported no evidence that "Mirt" IBS intervention reduced the risk of respiratory symptoms among older children in rural Ethiopia(12).…”
supporting
confidence: 83%
“…Then, when the parents of the household agreed to be involved in the study, the eld staff administered a written consent form at that time and the consent procedure was conducted in Amharic (both national & local language). It was also explained that the allocation to intervention or the control group was based on the concept of a "lottery" method, and several special efforts were applied during recruitment to facilitate the enrolment process as described within our earlier research report (23), and there was no any household unwilling to participate in the study.…”
Section: Sampling Methods and Recruitment Of Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, when the parents of the household agreed to be involved in the study, the field staff administered a written consent form at that time and the consent procedure was conducted in Amharic (both national & local language). It was also explained that the allocation to intervention or the control group was based on the concept of a "lottery" method, and several special efforts were applied during recruitment to facilitate the enrolment process as described within our earlier research report (23), and there was no any household unwilling to participate in the study.…”
Section: Sampling Methods and Recruitment Of Participantsmentioning
confidence: 99%